Ochrona tajemnicy zawodowej radcy prawnego i adwokata w polskim procesie karnym i cywilnym – uwagi krytyczne - Dąbrowski, Kamil (Acta Iuris Stetinensis, 2022)
Issues of attorney-client privilege are of interest to numerous representatives of the legal scholarship and commentary. Despite the bulk of controversies related to the specific nature of this institution, the literature relatively uniformly approaches its foundations, scope, and justification. Attorney-client privilege appears to be one of the basic guarantees of the implementation of the constitutional right to a fair trial. Hence, noticing the importance of this matter, this work also fits among the circle of publications focusing on this subject. However, it does not constitute a comprehensive study, but – through the analysis of the binding constitutional and statutory regulations – it aims to highlight the shortcomings of the legislative solutions in force, the existence of which may in the near future deprive the institution of the attorney-client privilege of the role of a real guarantee of protection of individual rights. With this purpose in mind, the discussion herein was constructed using the method of examination of the law in force, that is a detailed analysis of texts of binding legal acts.